Window display in a storefront helps enhances the image of a store to attract customers / Kamal Hussin Abdul Hamid - Abdul Hamid, Kamal Hussin (Faculty of Architecture, Planning and Surveying, 1991)
Good displays are primarily designed to sell merchandise, but they also create an atmosphere that indicates the character of the store. For example a prestige department store stresses elegance and high styling in its displays to convey the type of merchandise it carries. On the other hand a supermarket covers its windows with signs anniuncing sales and markdowns, which creates the impression that it is a store for bargain hunters. Good interior displays create a pleasing environment for clientele. Tasteful displays make customers feel that the store is providing a pleasant place for them to shop and make the employees feel that the store is interested in them because it provides an attractive place to work. Window display that are used to increase the sale of merchandise are called promotional displays. The great majority of window display are set-up purposely for promotional i.e to sell products. Window display function as an institutional displays because they sell the instituition or store as a whole and thewy also build customer goodwill.